Fabric-based patchwork on shoes through ultrasonic welding - Rahima Hussain; Muhammad Anwaar Nazeer (Journal of Engineered Fibers and Fabrics)
There has been a surge in textile and shoe product design innovation, introducing new products that merge design and technology in various domains. Decorative or functional patches on shoes are typically attached using stitching or adhesives, both of which present challenges: stitches often fail due to wear and tear, while adhesives involve toxic materials that are environmentally harmful. This study addresses these issues by exploring ultrasonic welding as a sustainable alternative for attaching patches to fabric shoes. The research aims to assess the impact of washing on the dimensional stability of the developed samples, investigate the ultrasonic seam strength of various fabric combinations, evaluate comfort properties, and examine the abrasion resistance of the attached patches. Results showed that PP-PP combinations exhibited the highest seam strength (55.3 N), as well as the highest air permeability (342 mm/s), making them ideal for application focused on strength and stability. However, PES-PES combinations demonstrated superior elongation (122.65%) and abrasion resistance (withstanding 35,000 cycles), proving suitable for flexibility and durability. Performance evaluation highlights ultrasonic welding as a more durable, environmentally friendly, and sustainable solution compared to conventional methods.